2021
DOI: 10.48550/arxiv.2107.02882
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Twin-width and polynomial kernels

Abstract: We study the existence of polynomial kernels, for parameterized problems without a polynomial kernel on general graphs, when restricted to graphs of bounded twin-width. Our main result is that a polynomial kernel for k-Dominating Set on graphs of twin-width at most 4 would contradict a standard complexity-theoretic assumption. The reduction is quite involved, especially to get the twin-width upper bound down to 4, and can be tweaked to work for Connected k-Dominating Set and Total k-Dominating Set (albeit with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The notion of twin-width was introduced very recently by Bonnet et al in [5], and has immediately gathered immense interest. As shown in [5] and in multiple subsequent works [1,2,3,4,6,10,11], twin-width is a versatile measure of complexity not only for matrices, but also for permutations and for graphs by considering a suitable matrix representation, which in the latter case is just the adjacency matrix. In particular, for every fixed t ∈ N, graphs excluding K t as a minor and graphs having cliquewidth at most t have bounded twin-width, which means that the concept of boundedness of twin-width is a vast generalization of boundedness of cliquewidth that does not assume tree-likeness of the structure of the graph.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The notion of twin-width was introduced very recently by Bonnet et al in [5], and has immediately gathered immense interest. As shown in [5] and in multiple subsequent works [1,2,3,4,6,10,11], twin-width is a versatile measure of complexity not only for matrices, but also for permutations and for graphs by considering a suitable matrix representation, which in the latter case is just the adjacency matrix. In particular, for every fixed t ∈ N, graphs excluding K t as a minor and graphs having cliquewidth at most t have bounded twin-width, which means that the concept of boundedness of twin-width is a vast generalization of boundedness of cliquewidth that does not assume tree-likeness of the structure of the graph.…”
Section: Introductionmentioning
confidence: 97%
“…In particular, for every fixed t ∈ N, graphs excluding K t as a minor and graphs having cliquewidth at most t have bounded twin-width, which means that the concept of boundedness of twin-width is a vast generalization of boundedness of cliquewidth that does not assume tree-likeness of the structure of the graph. As shown in the aforementioned works, this generalization is combinatorially rich [1,5,10], algorithmically useful [2,4,5], and exposes deep connections with notions studied in finite model theory [3,5,6,11]. In particular, assuming a suitable contraction sequence is provided on input, model-checking First-Order logic on graphs of bounded twin-width can be done in linear fixed-parameter time [5].…”
Section: Introductionmentioning
confidence: 98%
“…It has been shown that every graph class of bounded twin-width is small 3 [4], χ-bounded [5], and admits a linear-time algorithm for first-order model checking [8] (if we are given a certificate for an input graph to have small twin-width). Despite being a relatively new concept, twin-width has already generated a large amount of interests [8,4,5,6,13,7,1,10,17,9].…”
Section: Introductionmentioning
confidence: 99%